Implementation of Advertising in Kuantan Singingi Regency - Sari, Nilam; As’ari, Hasim (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The implementation of advertising in the Kuantan Singingi Regency involves several parties who form collaboration between parties. Organizing advertisements is a medium for promoting/introducing goods or services for entrepreneurs to influence the community in Kuantan Singingi Regency. However, many advertisements installed in Kuantan Singingi Regency still violate the applicable rules/regulations. This research aims to analyze and identify the implementation of advertising in Kuantan Singingi Regency and its obstacles. This research is a type of qualitative research that is descriptive in nature. The theory used in this research is the policy implementation model according to Thomas B. Smith (Syarief, 2019) which has four indicators, namely, idealized policy, target groups, implementing organization, and factors environment. The results of this research show that the implementation of advertising in Kuantan Singingi Regency has not been carried out in accordance with the Kuantan Singingi Regency Regional Regulation Number 5 of 2011 concerning Advertisement Tax and the Regent's Regulation of Kuantan Singingi Regency Number 46 of 2013 concerning Guidelines for the Implementation of Regional Regulation No. 5 of 2011. Obstacles faced faced in implementing this policy is that there are no workshops or technical guidance for implementers, no socialization and lack of awareness from advertising organizers.